Black Mothers’ Experiences of Having a Preterm Infant: A Scoping Review - Priscilla N. Boakye; Nadia Prendergast; Ola Abanta Thomas Obewu; Victoria Hayrabedian (Women)
Black mothers with preterm infants face unique challenges during their stay in the NICU and after discharge. Racism-related barriers impact access to care for Black preterm infants. Understanding their experiences in caring for preterm infants is crucial to developing equity-focused interventions to address racism in the NICU and promote Black preterm infant health outcomes. The purpose of this scoping review is to shed light on Black mothers’ experiences of having a preterm infant. A search was conducted in CINAHL, Medline, Maternity and Infant Care, and Google Scholar. A total of 287 articles were retrieved and screened. Twelve (12) articles included in the final review were from the United States. The findings highlight the need to address racism among healthcare providers in the NICU through training and education. Gaps in understanding the experiences of Black parents with preterm infants from other Western contexts remain and require further research.